2016
DOI: 10.1097/j.pain.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

GluN2B N-methyl-D-aspartate receptor and excitatory amino acid transporter 3 are upregulated in primary sensory neurons after 7 days of morphine administration in rats

Abstract: The contribution of the peripheral nervous system to opiate-induced hyperalgesia (OIH) is not well understood. Here, we determined the changes in excitability of primary sensory neurons after sustained morphine administration for 7 days. Changes in expression of glutamate receptors and glutamate transporters after morphine administration were ascertained in dorsal root ganglions (DRGs). Patch clamp recordings from intact DRGs (ex-vivo preparation) of morphine-treated rats showed increased excitability of small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 89 publications
1
14
0
1
Order By: Relevance
“…Similar to our findings, Kerui GongM demonstrated that sustained administration of morphine for seven days resulted in hyperalgesia and upregulated EAAT3 in dorsal root ganglia neurons. 36 Previous studies of neuropathic pain also reported that spinal EAAT3 exhibits a biphasic change following chronic constriction nerve injury (CCI), with an initial upregulation followed by downregulation. 13 , 37 An explanation for EAAT3 downregulation may be that CCI results in degenerative changes in primary afferents.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to our findings, Kerui GongM demonstrated that sustained administration of morphine for seven days resulted in hyperalgesia and upregulated EAAT3 in dorsal root ganglia neurons. 36 Previous studies of neuropathic pain also reported that spinal EAAT3 exhibits a biphasic change following chronic constriction nerve injury (CCI), with an initial upregulation followed by downregulation. 13 , 37 An explanation for EAAT3 downregulation may be that CCI results in degenerative changes in primary afferents.…”
Section: Discussionmentioning
confidence: 98%
“…The phosphorylation of MAPK family and the activation of glial cells in spinal dorsal horn induced by intraoperative remifentanil infusion can result in the production and release of multiple inflammatory mediators, and produce RIH [7, 3638]. In addition to glia, the phosphorylation and activation of NMDAR in spinal neurons also resulted in the synaptic plasticity and enhanced sensory responses after intraoperative remifentanil infusion [4, 3941]. The present study found that NAC can effectively decrease the phosphorylation of NR1, NR2B and MAPK family, decrease sensory neuron excitability and inhibit glial activation in spinal dorsal horn caused by remifentanil infusion.…”
Section: Discussionmentioning
confidence: 99%
“…35, 36 Briefly, rats were anaesthetized with sodium pentobarbital (40 mg/kg, i.p.). A lumbar laminectomy was performed; the L4 and L5 DRGs were removed and placed into carbogenized artificial cerebrospinal fluid (aCSF).…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies have linked OIH to specific molecular changes involving the N-methyl-D-aspartate (NMDA) receptor, glutamate transporters, adenosine-A1 receptor, serotonin receptor, K+/Cl- co-transporter, transient receptor potential vanilloid 1 (TRPV1), ephrinB receptor, intracellular messenger molecules including mammalian target of rapamycin (mTOR), protein kinase A (PKA) and calcium/calmodulin-dependent protein kinase II (CaMKII), as well as epigenetic mechanisms. 2, 3, 35, 54, 76 …”
Section: Introductionmentioning
confidence: 99%